Microvascular anastomotic coupler devices versus hand-sewn technique for arterial anastomosis: a systematic review. Issue 5 (June 2021) - Adam, D.; Broderick, D.; Kyzas, P.; Vassiliou, L.
Abstract: The use of microvascular anastomotic coupling devices (MACD) is an established technique for venous anastomosis. However, literature on arterial MACD is conflicting. We report, to our knowledge, the first registered systematic review of its kind to evaluate the safety and efficiency of arterial MACD in free flaps. We performed a PRISMA-guided systematic review (PROSPERO-registered) and identified reports using a search algorithm in MEDLINE/EMBASE. The rate of arterial thrombosis was set as the primary outcome. Secondary outcomes included flap survival, failure rates, and comparison of MACD and the conventional hand-sewn technique. From the 17 studies identified, 2672 free flap reconstructions were performed and 640 arterial anastomoses with MACD attempted (622 completed, 97.2%). The pooled incidence of arterial thrombosis was 2.1% (13/622), and overall flap failure rate 4.34% (116/2672). The total number of arterial MACD procedures performed first time, with no perioperative complications, revisions, or thrombosis, was 88.9% (569/640). Grading of Recommendations, Assessment, Development and Evaluation (GRADE) quality analysis revealed low quality and significant heterogeneity. The use of arterial MACD is a safe and efficient alternative to hand-sewn anastomosis, with more recent literature showing excellent results. However, further evaluation is required with controlled trials.